Legislating Gender Prejudice: Religion and the Overturning of Roe v Wade - Rena MacLeod (Australian Journal of Law & Religion)
This paper explores the intersection of religion, gender identity, and gender prejudice within the American context of religious conservatism and the overturning of Roe v Wade. Discussion considers the overturning as a dangerous move that negates the rights and religious liberties of women, with adverse implications also for the rainbow community. Notably, this legislative context depicts the power of conservative Christian ideology to sustain hierarchical gender norms anchored in a binary consciousness, which privileges and empowers men (typically white, elite, heterosexual men), while diminishing and disempowering women and gender-diverse persons as non-normative and subsidiary. Discussion further conveys that this male-centred/androcentric ideology continues the oppressive legacy of male-dominant, fundamentalist biblical interpretation — a mode of interpretation heavily criticised within contemporary mainstream biblical scholarship as flawed and grievous in its promotion of gender prejudice. Accordingly, the overturning of Roe v Wade is relevant to the Australian context, for the same androcentricity and legacy of biblically-justified gender prejudice underpins all Western cultures. That is, manifold people, knowingly or reflexively, religious or otherwise, adhere to this biased interpretation and prejudicial gender consciousness through entrenched psychosocial Western norms. Not least, much scholarship has stressed that the issue of gender bias deeply pervades the structures of Australia’s justice system. Ultimately, this paper emphasises that understanding androcentricity and the legacy of injurious androcentric biblical interpretation is necessary to the tasks of negotiating religious freedom for all persons and cultivating non-sexist social and legal structures that uphold the rights of multiple gender identities and subjectivities.